2010
DOI: 10.1038/ismej.2010.165
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing reveals highly diverse and species-specific microbial communities in sponges from the Red Sea

Abstract: Marine sponges are associated with a remarkable array of microorganisms. Using a tag pyrosequencing technology, this study was the first to investigate in depth the microbial communities associated with three Red Sea sponges, Hyrtios erectus, Stylissa carteri and Xestospongia testudinaria. We revealed highly diverse sponge-associated bacterial communities with up to 1000 microbial operational taxonomic units (OTUs) and richness estimates of up to 2000 species. Altogether, 26 bacterial phyla were detected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
261
5
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(306 citation statements)
references
References 74 publications
(80 reference statements)
33
261
5
5
Order By: Relevance
“…Sponge-specific and species-specific symbiont associations Our analyses confirmed a clear sponge-specific and species-specific signature of bacterial community composition, in agreement with previous studies employing less sequencing coverage (Webster et al, 2010;Erwin et al, 2011Erwin et al, , 2012Lee et al, 2011;Webster and Taylor, 2012). Sponge samples stored in a variety of ways also clustered by species, suggesting the signal override the preservatives, as previously shown (Simister et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Sponge-specific and species-specific symbiont associations Our analyses confirmed a clear sponge-specific and species-specific signature of bacterial community composition, in agreement with previous studies employing less sequencing coverage (Webster et al, 2010;Erwin et al, 2011Erwin et al, , 2012Lee et al, 2011;Webster and Taylor, 2012). Sponge samples stored in a variety of ways also clustered by species, suggesting the signal override the preservatives, as previously shown (Simister et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…Deep sequencing with next-generation platforms has revealed bacterial diversity that is unparalleled in any invertebrate host and approaches the complexity of the human gut (Webster et al, 2010). In line with the previously described 'spongespecific' clusters (Hentschel et al, 2002;Taylor et al, 2007a), studies using next-generation sequencing have shown sponge-specific bacterial communities in a number of sponge species (Lee et al, 2011;Schmitt et al, 2012). In addition, the observation of specific microbial communities at finer host phylogenetic levels, for example, within each sponge species (Lee et al, 2011), suggests potential host-symbiont co-speciation.…”
Section: Introductionmentioning
confidence: 76%
“…Similar results were obtained in previous studies, which found that Proteobacteria were the dominant members of wastewater microbial communities [15][16][17][18][19]. Previous studies also suggested that the most diverse group of bacteria in 6-and 12-dayold biofilms was Proteobacteria [20][21]. The Gramnegative Proteobacteria are a major group of bacteria encompassing a wide variety of aerobic, anaerobic, and facultative bacteria [22] that are able to degrade a broad spectrum of organic contaminants and enable biological nitrogen and phosphorus removal [23].…”
Section: Bacterial Community Structures In the Combinedsupporting
confidence: 79%
“…This was also the first study on Red Sea sponges with a very high number of selected clones. Phyla commonly associated with marine sponges dominated in the microbial community of A. willeyana (Taylor et al 2007; however, these phyla were significantly differentiated from the communities associated with other Red Sea sponges that had previously been studied using a similar 16S rRNA cloning approach (Hentschel et al 2002, Oren et al 2005, Radwan et al 2010, Lee et al 2011. The level of diversity could be compared with the microbiota of Red Sea Hyrtios erectus (42 selected clones), but this symbiotic community revealed members of Bacteroidetes, Firmicutes, TM7, and Betaproteobacteria (Radwan et al 2010), and lacked bacteria of an uncertain affiliation that were found in the Red Sea A. willeyana.…”
Section: Discussionmentioning
confidence: 96%
“…However, from among the ca. 240 sponge species recorded from the Red Sea (Radwan et al 2010), the microbial communities of only a few species have been investigated to date (Hentschel et al 2002, Oren et al 2005, Radwan et al 2010, Lee et al 2011. Our investigations on the microbial community of A. willeyana gave the first ever insight into the microbiota of coralline sponges from the Red Sea.…”
Section: Discussionmentioning
confidence: 98%